Utilizing Experiential Learning to Improve Financial Literacy Among Young Adults Through STEM Service-Learning Activity During Movement Control Order - Misiran, Masnita; Ahmad, Nazihah; Md Yusof, Zahayu; Abdul Rahim, Ummi Rohaizad (Universiti Malaya, 2022)
Financial education in the community is an important aspect of developing a good human and society. Sustainable development should be able to mobilize every individual in the community and the country to work together toward a more economicsustained lifestyle for every individual. Many researchers suggested that financial attitude, parental financial socialization, and financial literacy have a positive and significant relationship with prudent financial management practices. In this study, we aim to construct a personal financial literacy program through a service-learning program under one of the mathematical courses (SQQM3024 Mathematical Modelling) in the university to ensure the sustainability of the program. This course is selected since it is one of the main subjects that need to be completed by BSc (Hon) Business Mathematics students and is normally enrolled by students in their final year, thus sufficient maturity in STEM-based knowledge is expected. The program will be developed by using the ExDiD method. The finding shows that the method can construct a structured program and the delivery of the program can effectively improve communication skills among team members, the exploration of data, brainstorming ideas, and delivery to targeted participants, making service learning an effective tool for sustainable personal financial literacy programs to improve the level of financial literacy in the community